The Influence of the Internal Control Unit and Internal Control on Good University Governance at the Muhammadiyah University of Sukabumi - Nurfatimah, Riva; Himawan, Irfan Sophan; Noor, Iqbal (Journal of Management, Economic, and Accounting, 2023)
This study aims to examine the effect of the internal control unit and internal control on good university governance. This research is focused on the Muhammadiyah University of Sukabumi. This study uses a quantitative method with an associative approach. While the population in this study were SPI (internal audit unit) and all employees of the Muhammadiyah University of Sukabumi. The sampling technique uses a non-probability sampling method with a purposive sampling technique. This study tested its validity and reliability, the analysis techniques used were normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, and test the coefficient of determination. With the results of the internal control unit on good university governance has a significant effect, with a significance of 0.000 <0.05 and according to calculations, t count > t table is 6.491 > 1.997, internal control has an effect on good university governance with a significance of 0.001 <0.05, with calculations t count 3.337 > 1.997, and the unit of internal control and internal control has a simultaneous effect on good university governance with a significance of 0.000 <0.05 and according to the calculation of f count, f count > f table is 104.616 > 3.14.